Tendencies of the International Labor Migration in the Conditions of Globalization of the Central Asian Region - M., Myrzakhmetova A.; E., Aitbaev E. (Farabi Journal of Social Sciences, 2019)
Abstract. Article is devoted to the analysis of features, problems and factors of the international labor migration in the countries of the Central Asia (CA) and development of recommendations about improvement of regulation of this process in Kazakhstan. Article analyzes changes, tendencies and the directions of labor migration in the countries of the region. If at first these streams had a form of the compelled migration, further passed into scales of legal and illegal labor migration to such countries as Russia and Kazakhstan. Today the decrease in labor migration in these countries connected with devaluation of the Russian and Kazakhstan currency is noted. After all the factor of earnings moves workers from Central Asia, and no changes in the labor and migratory legislation of the host country influence so strongly migrants, as indicators of correction of currencies.